Pioneer plants of calcareous land in its early succession and the existence of Arbuscular Mycorrhizal Fungi - SUHARNO SUHARNO; SUPENI SUFAATI; DEWI WULANDARI; MUHAMMAD BONDAN ALFARABBI; SHERLITA MAULANI; ANNISA ALFAADHILAH RUHANI (Society for Indonesian Biodiversity, 2023)
Abstract. Suharno, Sufaati S, Wulandari D, Alfarabbi MB, Maulani S, Ruhani AA. 2023. Pioneer plants of calcareous land in its early succession and the existence of Arbuscular Mycorrhizal Fungi. Biodiversitas 24: 6209-6217. Calcareous land is characterized with the high presence of calcium carbonate and classified as marginal land because it does not have the quality to support plant growth. The soil quality in calcareous land is poor physically, chemically, and biologically. Nonetheless, certain plants and Arbuscular Mycorrhizal Fungi (AMF) thrive in this area. This research aims to determine plant diversity and the existence of AMF on calcareous land in Jayapura City, Papua, Indonesia. Data were collected through field observations in former limestone mining areas for a year. The results show that 41 types of plants were found at the study site. Based on the important value index, the most important plants were Bidens pilosa, Borreria sp., Piper aduncum, Pteris vittata, Polystichum sp., Axonopus compressus, Muntingia calabura, Pteris cretica, Cynodon sp., and Eleusine indica. Family with the largest number of species were Poaceae followed by Fabaceae, Pteridaceae, Moraceae, and Asteraceae. Based on plant habitus, 14.64% were ferns, 34.15% grasses, 39.62% herbaceous plants, and 12.20% trees. Plants sampled for the presence of AMF included B. pilosa, M. calabura, and P. aduncum. These plant species had level of AMF colonization of 71.2, 71.4, and 63.3%, respectively. There were 13 morphospecies of AMF belonging to the genera Glomus (46.15%), Claroideoglomus (7.69%), Acaulospora (38.46%), and Scutellospora (7.69%). The mutually beneficial symbiotic relationship between plants and AMF can be capitalized for managing the revegetation of former mining land with calcareous soil.